New upstream solution for mercury removal from petroleum condensate via HFMC: Thermodynamics, kinetics, DFT and mass transport - Poolkaew, Waranya; Mohdee, Vanee; Purktimatanont, Kittamuk; Pancharoen, Ura; Punyain, Wikorn; Lothongkum, Anchaleeporn W. (My University, 2023)
This work presents a new solution for the removal of mercury from petroleum condensate via hollow fiber membrane contactor (HFMC), which follows the principles and practices of solvent extraction. Results demonstrate that mercury can be successfully removed from petroleum condensate feed by the synergistic mixture solution of HCl and thiourea as extractant. Under equal circulating flow rates of 1.67 cm3 s−1 of feed and the synergistic extractant (0.5 mol dm−3 HCl and 1.5 mol dm−3 thiourea) at 323.15 K, the percentage of mercury removal reached 98.4%. The values of ∆H° (120 kJ mol−1), ∆S° (0.37 kJ mol−1) and ∆G° (−1.15 kJ mol−1) indicate that the reaction is endothermic, irreversible and spontaneous at 323.15 K, respectively. The results of Fourier-transform infrared spectroscopy (FTIR) confirm that mercury has been removed and is consistent with the obtained reaction mechanism from density functional theory (DFT). To describe the mass transport through HFMC, two mass transport mathematical models corresponding to reaction flux and diffusion flux are considered. The reaction flux model is seen to fit in well with the experimental results. The mass transfer coefficients in the membrane phase (km) and shell side (ks) are 7.45 × 10−6 cm s−1 and 2.09 × 10−5 cm s−1, respectively indicating that the mass transfer in the membrane phase is the controlling step.
Keywords: DFT; Hollow fiber membrane contactor; Mass transport; Mercury removal; Petroleum condensate